Beckman custom microcircuit voltage regulator with paper clip - Dietrich, T. A. (1950)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products, in this case a voltage regulator.
Keywords: Voltage regulators; Beckman Instruments, Inc.; Paper clips